HUKUM YANG MEMPERLAKUKAN ORANG “TIDAK SAMA” DI HADAPAN HUKUM (ITS REALITY: EVERYONE NOT EQUALITY BEFORE THE - Fitria, Yenni; Wibowo, Adhi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Equality before the law is one of the most fundamental normative principles or principles. This means that the law does not discriminate against anyone who comes to ask for justice. That is the ideal of law, that is the law that should be enforced anytime and anywhere. Meanwhile, in reality, we see that there is another principle that is looming, as we often hear in the expression